Degradation of aniline by electrochemical activation of peroxydisulfate at MWCNT cathode: The proofed concept of nonradical oxidation process. - Nie, C.; Ao, Z.; Duan, X.; Wang, C.; Wang, Shaobin; An, T. (Elsevier, 2018)
Enhanced elimination of aniline in aqueous solution was achieved by coupling electrosorption of aniline and electrochemical activation of peroxydisulfate (PDS) at multi-walled carbon nanotube (MWCNT) cathode, in which a synergistic effect occurred. It was found that PDS could be effectively activated under a small voltage at MWCNT cathode owing to the specific pore structures of MWCNTs. A nonradical oxidation pathway instead of radical-based oxidation was proposed from the cathodic activation of PDS, wherein PDS molecules with a modified electronic structure was suggested to be the principal reactive species. Meanwhile, the influences of various operation parameters such as electrode potential, PDS concentration, presence of chloride ions on the elimination efficiency, and the stability of MWCNT electrode were also attempted. Therefore, the electrochemical activation of PDS by MWCNT cathode is a promising energy-saving method for the treatment of organic pollutants in wastewater.